Inflammatory Regulation by Driving Microglial M2 Polarization: Neuroprotective Effects of Cannabinoid Receptor-2 Activation in Intracerebral Hemorrhage - Lin, Li; Yihao, Tao; Zhou, Feng; Yin, Niu; Qiang, Tan; Haowen, Zheng; Qianwei, Chen; Jun, Tang; Yuan, Zhang; Gang, Zhu; Hua, Feng; Yunfeng, Yang; et al. (Frontiers in Immunology, 2017)
The cannabinoid receptor-2 (CB2R) was initially thought to be the ‘peripheral cannabinoid receptor’. Recent studies, however, have documented CB2R expression in the brain in both glial and neuronal cells, and increasing evidence suggests an important role for CB2R in the central nervous system inflammatory response. Intracerebral hemorrhage (ICH), which occurs when a diseased cerebral vessel ruptures, accounts for 10–15% of all strokes. Although surgical techniques have significantly advanced in the past two decades, ICH continues to have a high mortality rate. The aim of this study was to investigate the therapeutic effects of CB2R stimulation in acute phase after experimental ICH in rats and its related mechanisms. Data showed that stimulation of CB2R using a selective agonist, JWH133, ameliorated brain edema, brain damage and neuron death, and improved neurobehavioral outcomes in acute phase after ICH. The neuroprotective effects were prevented by SR144528, a selective CB2R inhibitor. Additionally, JWH133 suppressed neuroinflammation and up-regulated the expression of microglial M2-associated marker in both gene and protein level. Furthermore, the expression of phosphorylated cAMP-dependent protein kinase (pPKA) and its downstream effector, cAMP-response element binding protein (CREB), were facilitated. Knockdown of CREB significantly inversed the increase of M2 polarization in microglia, indicating that the JWH133-mediated anti-inflammatory effects are closely associated with PKA/CREB signaling pathway. These findings demonstrated that CB2R stimulation significantly protected the brain damage and suppressed neuroinflammation by promoting the acquisition of microglial M2 phenotype in acute stage after ICH. Taken together, this study provided mechanism insight into neuroprotective effects by CB2R stimulation after ICH.